Penerapan Metode MOORA dan WASPAS dalam Keputusan Pemilihan Lokasi Usaha Laundry - Sanwani Sanwani; Pristiwanto Pristiwanto; Mesran Mesran; Sarwandi Sarwandi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The location of the Laundry business is a means of building a business, namely the place where the business is founded. Competition in this Laundry business causes many things to be considered in choosing a Laundry business location because if you don't choose the right location for a Laundry business, it can cause many losses such as bankruptcy for business owners. For this reason, business owners need foresight when setting up their Laundry business. To assist entrepreneurs in making decisions regarding the selection of a Laundry business location, there is a system that can be used, namely SPK. Decision Support Systems (DSS) are the steps or stages in finding a solution to a problem where the process is carried out using a solution according to how the computer works. There are 2 methods used in this study, namely the MOORA and WASPAS methods. The MOORA method is a method that can be used in the completion and completion process of the DSS. This method has a working procedure that uses mathematical calculations. While the WASPAS method is to find the priority of the most suitable location choice by using weighting. Where the results of research using the Multi-Objective Optimization by Ratio Analysis (MOORA) method, that which meets the criteria as the best Laundry business location is alternative A1, namely Jalan Setia Budi with a value of 0.2780 as the first rank. Meanwhile, based on the WASPAS method that meets the criteria as the best Laundry business location, alternative A7 is Jalan Gatot Subroto with a value of 0.8407 as the first rank.